2013
DOI: 10.2337/db12-1067
|View full text |Cite
|
Sign up to set email alerts
|

G6PC2: A Negative Regulator of Basal Glucose-Stimulated Insulin Secretion

Abstract: Elevated fasting blood glucose (FBG) is associated with increased risk for the development of type 2 diabetes and cardiovascular-associated mortality. Genome-wide association studies (GWAS) have linked polymorphisms in G6PC2 with variations in FBG and body fat, although not insulin sensitivity or glucose tolerance. G6PC2 encodes an islet-specific, endoplasmic reticulum–resident glucose-6-phosphatase catalytic subunit. A combination of in situ perfused pancreas, in vitro isolated islet, and in vivo analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(141 citation statements)
references
References 42 publications
(75 reference statements)
20
121
0
Order By: Relevance
“…GSE72719) (Ingenuity Pathway Analysis presented in Supplementary Table 4). Interestingly, G6pc2, one of the most highly expressed genes in β-cells (9), was strongly repressed in islets from SRI-tg10 mice. Subsequent qRT-PCR analysis in isolated islets from SRI-tg10, SRI-tg1, and Sri −/− mice confirmed the inverse relationship between Sri and G6pc2 expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GSE72719) (Ingenuity Pathway Analysis presented in Supplementary Table 4). Interestingly, G6pc2, one of the most highly expressed genes in β-cells (9), was strongly repressed in islets from SRI-tg10 mice. Subsequent qRT-PCR analysis in isolated islets from SRI-tg10, SRI-tg1, and Sri −/− mice confirmed the inverse relationship between Sri and G6pc2 expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, key metabolic genes that are either considered 'disallowed' or contribute to their regulation (Dhawan et al, 2015;MartinezSanchez et al, 2016;Piccand et al, 2014;Pullen and Rutter, 2013) were enriched in immature beta cells ( Figure 3E). Islets were also co-stained for insulin, Ucn3, and 8 G6pc2, which hydrolyzes glucose-6-phosphate (Pound et al, 2013) or the oxidoreductase Ero1lb, which is required for disulfide bond formation in pro-insulin (Zito et al, 2010). Both markers co-labeled Ucn3-positive mature beta cells, and the majority of Ucn3 negative beta cells did not express G6pc2 or Ero1lb ( Figure 3F-I).…”
Section: Ucn3 Negative Beta Cells Are Transcriptionally Immaturementioning
confidence: 99%
“…This variant has in previous studies been found to be associated with elevated fasting glucose [15] and it likely regulates the expression of G6PC2 encoding the catalytic subunit of glucose-6-phosphatase, a regulator of glycolytic flux in the beta cell. The major allele is proposed to cause a rightward shift of the dose-response curve for the glucosestimulated insulin secretion [16], which explains the association with HOMA-B and insulinogenic index in opposite directions.…”
Section: Discussionmentioning
confidence: 99%